PROFIL PEMUSTAKA LAYANAN PERPUSTAKAAN FAKULTAS USHULUDDIN IAIN IMAM BONJOL PADANG - Reza Fahmi (UIN Imam Bonjol Padang, 2017)
Abstract: This research departs from the awareness that libraries are vital instruments for a tertiary institution. One important element in measuring the quality of a library is the services provided at the library. Furthermore, this study aims to: (1) Obtain an overview of the Ushuluddin Faculty IAIN Imam Bonjol Padang library. (2) Obtaining an overview of the various services carried out at the Faculty of Usuluddin. (3) Obtaining an overview of the library service user profile at the Faculty of Usuluddin IAIN Imam Bonjol Padang. This research uses a qualitative approach. Remember secondary data is used as the main source used in research carried out. Then as resource persons / informants in this study are: (1) library coordinator of the Faculty of Usuluddin. (2) library staff in the Faculty of Usuluddin. (3) Library library students of the Ushuluddin Faculty IAIN Imam Bonjol Padang. Data collection techniques are through documentation studies and interviews to supplement information obtained from various informants / informants in the research conducted. The data scaling technique is to use statistical tools, namely by using qualitative descriptive analysis. The results of this study found: (1) There are three main services for users provided by the Ushuluddin Faculty IAIN Imam Bonjol Padang library: (a) circulation services (b) reference services (c) internet services. (2) There is a significant increase in the number of users at the Faculty of Islamic Studies Imam Bonjol Padang IAIN between 2015 and 2016. (3) Those who use library services of the Faculty of Islamic Studies Ushuluddin IAIN Imam Bonjol Padang are generally male in 2015. While female visitors dominates the users of the Faculty of Usuluddin IAIN Imam Bonjol Padang in 2016 .. (4) Users who use the library of the Usshuluddin IAIN Faculty of Padang generally come from the Department of Islamic Psychology.Keywords: Library and Library Service,Abstrak : Penelitian ini berangkat dari kesadaran bahwa perpustakaan merupakan instrumen vital bagi sebuah perguruan tinggi. Salah satu unsur penting dalam mengukur kualitas perpustakaan adalah layanan yang diberikan pada perpustakaan tersebut. Lebih jauh penelitian ini bertujuan untuk : (1) Memperoleh gambaran tentang perpustakaan Fakultas Ushuluddin IAIN Imam Bonjol Padang. (2) Memperoleh gambaran tentang berbagai layanan yang dijalankan pada Fakultas Ushuluddin. (3) Memperoleh gambaran profil pengguna layanan perpustakaan di Fakultas Ushuluddin IAIN Imam Bonjol Padang. Penelitian ini menggunakan pendekatan kualitatif. Mengingat data-data skunder digunakan sebagai sumber utama yang digunakan dalam penelitian yang dijalankan. Kemudian sebagai nara sumber / informan dalam penelitian ini adalah : (1) koordinator pertpustakaan Fakultas Ushuluddin. (2) staf perpustakaan di Fakultas Ushuluddin. (3) Mahasiswa pemustaka perpustakaan Fakultas Ushuluddin IAIN Imam Bonjol Padang. Teknik pengumpulan data adalah melalui studi dokumentasi dan wawancara untuk melengkapi informasi yang diperoleh dari berbagai narasumber / informan dalam penelitian yang dijalankan. Teknik pengalisaan data adalah dengan menggunakan alat bantu statistik, yakni dengan menggunakan analisa deksriptif kualitatif. Hasil penelitian ini mendapati : (1) Terdapat tiga layanan utama bagi pemustaka yang diberikan oleh perpustakaan Fakultas Ushuluddin IAIN Imam Bonjol Padang : (a) layanan sirkulasi (b) layanan referensi (c) layanan internet. (2) Adanya peningkatan jumlah yang signifikan dari pemustaka di Fakultas Ushuluddin IAIN Imam Bonjol Padang antara tahun 2015 sampai dengan 2016. (3) Pemustaka yang menggunakan layanan perpustakaan Fakulas Ushuluddin IAIN Imam Bonjol padang umumnya adalah laki-laki pada tahun 2015. Sedangkan pemustaka perempuan mendominasi pengguna perpustakaan Fakultas Ushuluddin IAIN Imam Bonjol Padang tahun 2016.. (4) Pemustaka yang menggunakan perpustakaan Fakultas Ushuluddin IAIN Imam Bonjol Padang umumnya berasal dari Jurusan Psikologi Islam. Kata kunci : Pemustaka dan Layanan Perpustakaan,